Aplicación de los productos agrícolas del cantón Quero en tendencias gastronómicas de vanguardia - Carbajal Bautista, Cristopher Israel (2025)
This research work has focused on the use of cutting-edge techniques with local products from the Quero canton in the province of Tungurahua. This type of practice of gastronomic techniques over time has been considered very important and, above all, useful and with many benefits, because while a tourist visits us, he can eat properly, keeping his body in a healthy state, this is how it is important to use the agricultural products of the area to generate a sustainable economy within the canton. According to the bibliography, it was possible to identify authors who refer to the agricultural and livestock production sector, and the absence of works focused on gastronomy generates the need to create new gastronomic techniques. The methodology to develop the work and collect the required information was exploratory, descriptive, explanatory, crosssectional, applying instruments such as interviews and experimentation with avant-garde techniques with ingredients typical of the canton, anticipating the use of important techniques that without need for equipment or machinery that is difficult to obtain by the population. The results obtained are the proposal of 9 techniques used in local agricultural products, which could contribute to improving the quality of presentation and more attractive flavors to visitors to the area, generating an update in the sales options to the general public.